Factors Associated With a High Motivation to Undergo Fertility Preservation in Female Cancer Patients - Di Mattei, Valentina Elisabetta; Perego, Gaia; Taranto, Paola; Rancoita, Paola M. V.; Maglione, Mariangela; Notarianni, Lisa; Mangili, Giorgia; Bergamini, Alice; Cioffi, Raffaella; Papaleo, Enrico; Candiani, Massimo (Frontiers in Psychology, 2021)
Objective: Fertility loss due to cancer treatment can be a devastating experience for women and the couple. Undergoing fertility preservation can be a complex decision from both a medical and emotional point of view. The aim of the present study was to evaluate which socio-demographic and psychological factors predict a high motivation to undergo fertility preservation. Methods: Fifty-eight female cancer patients who accessed an Oncofertility Unit completed: a questionnaire to collect socio-demographic characteristics and the level of motivation, the Beck-Depression Inventory-II, the State-Trait Anxiety Inventory-Y, and the Fertility Problem Inventory. Results: Almost half of the sample (44.8%) declared a high motivation. At multiple logistic regression analysis only the “Need for parenthood” subscale of the FPI predicted a high motivation. We alternatively evaluated as possible predictor the construct “Representations about the importance of parenthood” (i.e., the sum of the “Need for Parenthood” and “Rejection of childfree lifestyle” subscales) in place of the two separate subscales. At multiple logistic regression analysis, only this variable predicted a high motivation to undergo fertility preservation. Conclusion: The most important predictor of a high motivation to undergo fertility preservation is the individual desire for parenthood. This implies that, regardless of socio-demographic characteristics, any woman of childbearing age should receive an appropriate counseling about fertility preservation.